Effects of an Educational Hybrid Physical Education Program on Physical Fitness, Body Composition and Sedentary and Physical Activity Times in Adolescents: The Seneb’s Enigma - Melero-Cañas, David; Morales-Baños, Vicente; Manzano-Sánchez, David; Navarro-Ardoy, Dani; Valero-Valenzuela, Alfonso (Frontiers in Psychology, 2021)
Physical activity (PA), body composition and sedentary behaviour may affect the health of children. Therefore, this study examined the effect of an educational hybrid physical education (PE) programme on physical fitness (PF), body composition and sedentary and PA times in adolescents. A 9-month group-randomized controlled trial was conducted in 150 participants (age: 14.63 ± 1.38 years) allocated into the control group (CG, n = 37) and experimental group (EG, n = 113). Cardiorespiratory fitness, speed, strength, agility, flexibility and body mass index (BMI) were assessed through previously validated field tests. Sedentary time, PA at school and afterschool were evaluated with the Youth Activity Profile-Spain questionnaire. Significant differences were observed with respect to the CG in APA-weekend (p = 0.044), speed-agility (p = 0.005) and agility (p = 0.008). Regarding the intervention, cardiorespiratory fitness (p = 0.000), speed-agility (p = 0.000), strength (p = 0.000), flexibility (p = 0.000), agility (p = 0.000), PA in school (p = 0.011), APA-weekday (p = 0.001), APA-weekend (p = 0.000), APA-week (p= 0.000) and sedentary time (p = 0.000) increased significantly in the EG. The use of a hybrid programme based on TPSR and gamification strategies produced enhancements in cardiorespiratory fitness, agility, speed, APA-weekdays and APA-weekends, reducing the sedentary time.